2017
DOI: 10.1016/j.aller.2017.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence and risk factors of allergic rhinitis symptoms in primary schoolchildren six years apart in Budapest

Abstract: Although the prevalence of physician-diagnosed AR has not shown significant changes during the studied interval, the significant increase of the current AR symptoms suggests growing prevalence of AR among children in Budapest. Our results revealed new aspects of bedding customs in atopic families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 24 publications
2
14
0
1
Order By: Relevance
“…For acetaminophen exposure in early life, the metaanalysis of 15 estimates from 11 studies [13,17,18,20,[26][27][28][29][31][32][33] (510,796 participants) showed significant associations between acetaminophen exposure and allergic rhinitis (OR: 1.34, 95% CI: 1.21-1.49) ( Fig. 2; Table 2).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
See 4 more Smart Citations
“…For acetaminophen exposure in early life, the metaanalysis of 15 estimates from 11 studies [13,17,18,20,[26][27][28][29][31][32][33] (510,796 participants) showed significant associations between acetaminophen exposure and allergic rhinitis (OR: 1.34, 95% CI: 1.21-1.49) ( Fig. 2; Table 2).…”
Section: Results Of Meta-analysismentioning
confidence: 99%
“…The 17 articles [13][14][15][16][17][18][19][20][26][27][28][29][30][31][32][33][34], including a total of 870,492 participants, were published from 2000 to 2018. Among the 18 studies included in the 17 articles, 5 were cohort studies [18][19][20]28], 2 were case-control studies [15,30], and 11 were cross-sectional studies [13,14,16,17,26,27,29,[31][32][33][34]. Six studies were conducted in Europe [15,17,20,27,32,34], 5 studies in Asia [18,29,31,33], 2 studies in Africa [16,28], 2 studies in Oceania [19,26], 1 study in South America…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations